2012
DOI: 10.1074/jbc.m111.308122
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Translation Elongation Factor 1A Induces Anoikis by Triggering Cell Detachment

Abstract: Background: Fibronectin harbors a cryptic antiadhesive site that is able to inactivate ␤-1 integrins. Results: Spontaneous anoikis of nontransformed fibroblasts was caused by exposure of this antiadhesive site and its recognition by membrane-resident eEF1A. Conclusion: eEF1A functions as a membrane receptor triggering cell detachment, resulting in anoikis.Significance: The results demonstrate a new function of eEF1A that contributes to cell regulation, including anoikis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…These results suggested that TNC stimulated cell proliferation through proteolytic exposure of the TNIIIA2-related cryptic proadhesive site of the TN-C molecule. We previously detected the secretion of an active form of MMP-2 from NIH3T3 cells (38). Moreover, the TN-C-induced stimulation of cell proliferation was inhibited by the function-blocking mAb directed to the integrin ␣5 subunit but not by mAbs directed to the ␣4 and ␣v subunits (Fig.…”
Section: Peptide Tniiia2 Renders Nih3t3 Cells Anoikis-resistant Andmentioning
confidence: 99%
“…These results suggested that TNC stimulated cell proliferation through proteolytic exposure of the TNIIIA2-related cryptic proadhesive site of the TN-C molecule. We previously detected the secretion of an active form of MMP-2 from NIH3T3 cells (38). Moreover, the TN-C-induced stimulation of cell proliferation was inhibited by the function-blocking mAb directed to the integrin ␣5 subunit but not by mAbs directed to the ␣4 and ␣v subunits (Fig.…”
Section: Peptide Tniiia2 Renders Nih3t3 Cells Anoikis-resistant Andmentioning
confidence: 99%
“…Recent evidences show eEF1A to act as a membrane receptor for the cryptic anti-adhesive site of fibronectin, which contributes to cell regulation, including anoikis, through negative modulation of cell anchorage. Possibly, the membrane-resident eEF1A may interact with beta1-integrins inactivating their functions in cell adhesion (Itagaki et al, 2012). Down-regulation of eEF1A1 seems to be specific to senescence.…”
Section: Functionmentioning
confidence: 99%
“…No other gene is present in the wasted deletion, and transgenic studies have shown that the EEF1A1 (eukaryotic translation elongation factor 1 alpha 1) Scaggiante B, Bosutti A Atlas Genet Cytogenet Oncol Haematol. 2015;19(4) phenotype is due to loss of eEF1A2 translation activity in muscle (Doig et al, 2013;Abbott et al, 2009). In neuronal cells, an eEF1A1 interaction with the yeast two-hybrid protein K (HYPK), highlights the involvement of HYPK in the regulation of cell growth, cell cycle, unfolded protein response and cell death.…”
Section: Skeletal Muscle Trauma and Motor Neuron Degenerationmentioning
confidence: 99%
See 2 more Smart Citations